Thermostablility of phycobiliproteins and antioxidant activity from four thermotolerant cyanobacteria - Pumas C. (2014)
Four cyanobacterial strains including Cyanosarcina sp. SK40, Phormidium sp. PD40-1, Scytonema sp. TP40 and Leptolyngbya sp. KC45 were selected and investigated for the phycobiliprotein (PBP) content and thermostable antioxidant activity of their cell-free extracts. The highest content of 181.63mg/g dry weight phycobiliprotein was found in Leptolyngbya sp. KC45 with phycoerythrin (PE) as the main phycobiliprotein. Among the PBPs of four thermotolerant cyanobacteria, PE from Leptolyngbya sp. KC45 exhibited the highest thermal stability as 80% of the original level remained after being heated at 60°C for 30min. Antioxidant activities were detected in the cell-free extracts of all cyanobacteria and that of Leptolyngbya sp. KC45 was also found in the highest value of 7.44±0.14 and 3.89±0.08mg gallic acid equivalent (GAE) g-1 dry weights determined by 2,2-diphenyl-1-picrylhydrazyl radical (DPPH) and reducing power assay, respectively. This also corresponded to the phenolic compound content. Based on DPPH and reducing power assay, antioxidant activities of all cyanobacterial extracts showed the high thermostability as approximately 80% remained after being heated at 80°C for 30min. However, it clearly indicated that the thermostability of antioxidant activity from the hot spring cyanobacterial cell-free extract was not contributed only by the PE, but also came from phenolic compounds and other oxidative substances. © 2011 Japanese Society of Phycology.